2013
DOI: 10.1136/annrheumdis-2012-202669
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound colour Doppler is associated with synovial pathology in biopsies from hand joints in rheumatoid arthritis patients: a cross-sectional study

Abstract: Colour Doppler activity is associated with the extent of inflammation present in the synovial biopsies from RA patients. However, synovial pathology was also seen in biopsies taken from Doppler negative sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 23 publications
8
31
0
Order By: Relevance
“…The absence of signalling on DUS scans does not rule out synovial cytokine production. These findings are in accord with the results of our previous study in which DUS-detected activity was compared to synovial histopathology in a similar group of RA patients [35]. That previous study did not include grading of the synovial hypertrophy, because the images were obtained only for evaluation of colour Doppler.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The absence of signalling on DUS scans does not rule out synovial cytokine production. These findings are in accord with the results of our previous study in which DUS-detected activity was compared to synovial histopathology in a similar group of RA patients [35]. That previous study did not include grading of the synovial hypertrophy, because the images were obtained only for evaluation of colour Doppler.…”
Section: Discussionsupporting
confidence: 90%
“…As Figure 1 shows, 25 patients were enrolled into the study, 12 of whom were recruited from a previous study [35]. Three patients who were offered participation declined, and an additional three patients were excluded on the basis of the US examination because of lack of synovial hypertrophy in the hand joints (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of MSUS in identifying inflammatory lesions is underpinned by correlations between the PD signal intensity and histopathology or contrast MRI of the same tissue [44,45,58,[61][62][63][64][65][66]. Both, synovial histopathology and MRI are considered 'gold standard' methods for joint/ peri-articular tissue examination.…”
Section: The Discriminative Capacity and Validity Of Msus In Ramentioning
confidence: 99%
“…Most of studies demonstrated how its reduction is an indicator of good treatment response, whereas its persistence reveals to be a negative predictor for the outcomes [2,4,5]. Although some data raised questions about the PD vulnerability in front of different aspects (i.e., like type of machine setting, exaggerate pressure of the probe, patient position, climatic conditions, the hour of the examination) [3,[6][7][8], PD is considered an accurate indicator of the activity of the inflammatory process in the synovial tissue. Despite this relevant role, at date, there are some controversies about the correlation between the presence of PD and the articular pain.…”
Section: Introductionmentioning
confidence: 99%